Drug Testing Balancing Privacy and Public Safety - DeCew, Judith Wagner (The Hastings Center report, 1994)
Although testing for substance abuse can be intrusive, inaccurate, and ineffective at ferreting out those who are a threat to others, it can be morally justified in certain carefully circumscribed cases.